Paradigm Shift in Teaching - Gayathri, J. (Indian Journal of Computer Science, 2024)
The paradigm shift in teaching involves embracing technology, fostering student-centered learning, and promoting interactive and collaborative methods to better engage and prepare students for the evolving demands of the future. Certainly, in this paradigm shift, traditional lecture based approaches are giving way to more experiential learning, incorporating real world applications and project-based assessments. Personalized learning pathways are gaining prominence, catering to individual student needs and learning styles. Additionally, the focus is shifting towards developing critical thinking, problem-solving, and digital literacy skills to prepare students for a rapidly changing global landscape. Assessment methods are evolving to emphasize understanding over memorization, encouraging a deeper grasp of concepts. Overall, the aim is to create a dynamic and adaptive educational environment.